The Political Economy of Chinese Investment in Cambodia - Chheang, Vannarith (ISEAS Publishing, 2017)
China suffers from a trust deficit in the region, and Southeast Asian countries have adopted hedging strategies, at varying degrees, aimed at diversifying their economic and strategic interests from Chinese investments and influence. Cambodia considers China as an important strategic and economic partner in providing performance legitimacy and as a countervailing force against its immediate neighbours. Cambodia's economic overdependence and power asymmetry have enabled China to exert significant political leverage over the Kingdom, especially on international issues affecting Chinas core national interest such as the South China Sea dispute. Local communities are discontented with some Chinese investment projects, especially hydropower plants and land concessions, which have infringed on labour rights and environmental protection. Given the public resentment and dynamic changes and transformations of politico-social environment in Cambodia, China needs to address the concerns and issues raised by local communities in order to sustain and enlarge its political and economic footprint. Promoting good corporate governance, as well as social and environmental responsibility, would help.